TiOx/Pt3Ti(111) surface-directed formation of electronically responsive supramolecular assemblies of tungsten oxide clusters - Moors, Marco; An, Yun; Kuc, Agnieszka; Monakhov, Kirill Yu. (Beilstein Journal of Nanotechnology, 2021)
Highly ordered titanium oxide films grown on a Pt3Ti(111) alloy surface were utilized for the controlled immobilization and tip-induced electric field-triggered electronic manipulation of nanoscopic W3O9 clusters. Depending on the operating conditions, two different stable oxide phases, z’-TiOx and w’-TiOx, were produced. These phases show a strong effect on the adsorption characteristics and reactivity of W3O9 clusters, which are formed as a result of thermal evaporation of WO3 powder on the complex TiOx/Pt3Ti(111) surfaces under ultra-high vacuum conditions. The physisorbed tritungsten nano-oxides were found as isolated single units located on the metallic attraction points or as supramolecular self-assemblies with a W3O9-capped hexagonal scaffold of W3O9 units. By applying scanning tunneling microscopy to the W3O9–(W3O9)6 structures, individual units underwent a tip-induced reduction to W3O8. At elevated temperatures, agglomeration and growth of large WO3 islands, which thickness is strongly limited to a maximum of two unit cells, were observed. The findings boost progress toward template-directed nucleation, growth, networking, and charge state manipulation of functional molecular nanostructures on surfaces using operando techniques.
Keywords: atom manipulation; scanning tunneling microscopy; supramolecular self-assemblies; titanium oxide; tungsten oxide